(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
In the article we have developed a method for creating new patterns and designs of Sarja, Satin (Atlas) T-shirts based on existing theory of welding techniques with the use of modern computerized cordless weaving machines. The peculiarity of this method of obtaining a knitting pattern is that under a certain law, a knitting Sarja, a torn-type Sarja, is chosen as a base. It is possible to obtain a new rotation pattern by placing the base axis in the coordinate arrows and diagonal arrows that are in between them. When creating a new knitting pattern, the base is formed by shifting the direction of movement of the joints, body, rope coatings in the base braiding cells. The base rotation placed in the center of the coordinate axis cannot be changed. The base around the obtissa and the ordinate and the diagonal axes are altered according to a specific law, until the design of the pattern is well polished. The base at the center of the coordinate axis indicates that the base bracket is reinforced once for all axes around the axis.In the second variant of the method, the rotation pattern is adjusted by rotating the rotation sliding or coating clockwise or to the right of the base around the center. It is shown that different patterns can be obtained using the methods mentioned above. There is also a formula for defining the pattern of body and weave braiding patterns in the formation of these joints.